THE IMAGE OF WOMEN AND THEIR ROLE IN SOCIETY IN THE WORKS OF JADIDS - Arapjonova Zebo Otabek qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article explores the portrayal of women and their societal roles in the literary and cultural works of the Jadid movement. The Jadids, as reformist intellectuals of the late 19th and early 20th centuries in Central Asia, advocated for modernization, education, and social reforms, including the advancement of women’s status. Through analysis of key texts and writings, this paper examines how Jadid authors depicted women as crucial agents of cultural renewal and social progress, emphasizing their education, emancipation, and moral influence within the family and society. The study highlights the complex and sometimes ambivalent perspectives on gender roles, reflecting both traditional values and progressive ideas characteristic of the Jadid reform agenda.